REVITALIZATION OF THE EARTH'S ALMS TRADITION WITH ISLAMIC RITUALS IN THE DIGITAL ERA - Muh Syauqi Malik; Arina Zulva Maulida; Maslahah Maslahah (The Pontianak State Institute of Islamic Studies, 2023)
Earth almsgiving is a tradition that has existed since the time of the ancestors in Indonesia. The tradition of the ancestors is a form of gratitude to God Almighty for the abundance of his grace in a certain region. Society must be able to distinguish between expressions of gratitude and destruction.Â This type of research is a qualitative case study in a certain society to thoroughly explore the benefits and meaningfulness of the essence of the earth's alms tradition that still needs to be maintained in the digital era. Data analysis techniques use data reduction, data presentation, conclusion drawing, and verification.Â The results showed that the earth alms tradition has a very strong Islamic philosophy and ritual, people must understand the essence of earth alms as a whole so as not to just follow the currents of the times. The factor that makes people want to hold the earth alms tradition is a form of gratitude for the abundance of grace from God Almighty. The tradition of earth almsgiving is not shirked nor is it to satisfy the lust of entertainment by holding a momentary feast, but must stick to Islamic rituals according to the sharia of the Prophet Muhammad SAW and the teachings of the saints along with the guidance of religious leaders in the region